Keterlibatan orang tua dalam pembelajaran daring selama pandemi covid-19 di sekolah dasar - Widyastuti Widyastuti; Sandra Bayu Kurniawan; Peduk Rintayati (Didaktika Dwija Indria, 2021)
This research was conducted to describe the meaning of parental involvement in online learning during the Covid-19 pandemic at SDN Gesikan Desa Gesikan in 2020. Parents have an important involvement in the online learning process carried out by children during the Covid-19 pandemic. Parental involvement includes providing facilities, motivation, and guiding online learning. This research is classified into qualitative research using a phenomenological approach. The subjects of this study were parents, students, and teachers at SDN Gesikan. The selection of research subjects was carried out by purposive sampling. Data collection techniques through observation, interviews, and documentation. Data analysis was performed using Miles and Hubeman through data collection, data reduction, and data verification. The data validity used source triangulation. The results showed that parents were involved in children's online learning during the Covid-19 pandemic. Parental involvement in the online learning process experienced by children includes providing facilities, motivation, and guidance. Parents feel sad about children's online learning due to the lack of explanation from the teacher.